PENGARUH APLIKASI TIK TOK TERHADAP EKSPRESI KOMUNIKASI MAHASISWA UNIVERSITAS ISLAM NEGERI (UIN) SUNAN AMPEL SURABAYA TAHUN 2020 - Sandi Pratama; Muchlis Muchlis (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This research aims to describe the influence of Tiktok's use of communication expressions of UIN Sunan Ampel Surabaya 2020. The number of samples taken in this study was as much as 94 people with purposive sampling techniques. This research is quantitative deskriftif research with correlation technique. The instrument used in this research is a poll of Tiktok's application and a poll of the influence of Tiktok on the communication expression UIN Sunan Ampel. Data is analyzed by using the Pearson product moment correlation. The research showed that there was a significance relationship between the use of Tiktok application with the influence of Tiktok on the communication expression of UIN Sunan Ampel Surabaya. which has a correlation coefficient value of 0.637 and the equivalent significance of P = 0,000 (P < 0.05) which means that the higher use of Tiktok application will be the higher expression of communication students UIN Sunan Ampel affected. Conversely, the lower the use of Tiktok application then the lower the effect.